Mesoporous boron-doped onion-like carbon as long-life oxygen electrode for sodium–oxygen batteries. Issue 17 (15th April 2016) - Shu, Chaozhu; Lin, Yangming; Zhang, Bingsen; Abd Hamid, Sharifah Bee; Su, Dangsheng
Abstract : Boron-doped onion-like carbon is successfully synthesized by calcination of ultra-dispersed nanodiamond and it exhibits excellent catalytic activity for the oxygen electrode reaction in Na–O2 batteries. Abstract : Metal–oxygen batteries are thought to be the ultimate energy storage solution due to their high specific energy. We report here on the synthesis of mesoporous boron-doped onion-like carbon (B-OLC) microspheres and their application in rechargeable sodium–oxygen (Na–O2 ) batteries. Low overpotential, high specific capacity (over 10 200 mA h g −1 ), enhanced rate capability (∼7500 mA h g −1 at 0.6 mA cm −2 ) and excellent cyclability (up to 125 cycles) can be achieved by using B-OLC based electrodes in Na–O2 batteries. The critical role of surface chemistry on the morphology and composition of products is studied and the optimum performance of Na–O2 batteries with B-OLC based electrodes is attributed to the synergistic effects arising from the combination of catalytic activity and the uniquely mesoporous carbon nanoarchitecture. This study indicates that mesoporous B-OLC demonstrated intriguing properties and great potential applications as effective metal-free bifunctional catalysts for Na–O2 batteries and encourages the development of heteroatom-doped carbon materials for performance improvement of metal–oxygen batteries.